2020
DOI: 10.3390/nu13010058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Carbohydrate Intake after Sprint Exercise on Breath Acetone Level

Abstract: Assessment of breath acetone level may be an alternative procedure to evaluate change in fat metabolism. The purpose of the present study was to investigate the effect of insufficient carbohydrate (CHO) intake after sprint exercise on breath acetone level during post-exercise. Nine subjects conducted two trials, consisting of either reduced CHO trial (LOW trial) or normal CHO trial (NOR trial). In each trial, subjects visited to laboratory at 7:30 following an overnight fast to assess baseline breath acetone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Some of the selected studies assessed higher levels of ketogenic metabolites in U-CD than in HC ( Bertini et al, 2009 ; Di Cagno et al, 2009 ; Bernini et al, 2011 ; Upadhyay et al, 2020 ). Similarly, Bertini et al (2009) analyzed the same subjects pre- and post-GFD and observed an inverse tendency in serum levels of β-hydroxybutyric acid, which is a ketone body usually increased during the fasting phase as an alternative energy source for brain activity ( Ota et al, 2021 ). Hence, the significant decrease of β-hydroxybutyric acid ( Bertini et al, 2009 ) seems to indicate the return to a normal energy metabolism via carbohydrates instead of ketone bodies driven by GFD.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the selected studies assessed higher levels of ketogenic metabolites in U-CD than in HC ( Bertini et al, 2009 ; Di Cagno et al, 2009 ; Bernini et al, 2011 ; Upadhyay et al, 2020 ). Similarly, Bertini et al (2009) analyzed the same subjects pre- and post-GFD and observed an inverse tendency in serum levels of β-hydroxybutyric acid, which is a ketone body usually increased during the fasting phase as an alternative energy source for brain activity ( Ota et al, 2021 ). Hence, the significant decrease of β-hydroxybutyric acid ( Bertini et al, 2009 ) seems to indicate the return to a normal energy metabolism via carbohydrates instead of ketone bodies driven by GFD.…”
Section: Discussionmentioning
confidence: 99%